2019
DOI: 10.1021/acs.est.9b01359
|View full text |Cite
|
Sign up to set email alerts
|

Tributyltin Affects Retinoid X Receptor-Mediated Lipid Metabolism in the Marine Rotifer Brachionus koreanus

Abstract: To examine how tributyltin (TBT), a model obesogen, affects the lipid metabolism in the marine rotifer Brachionus koreanus, we carried out life-cycle studies and determined the in vitro and in silico interactions of retinoid X receptor (RXR) with TBT, the transcriptional levels of RXR and lipid metabolic genes, and the fatty acid content. The lethal concentration 10% (LC10) was determined to be 5.12 μg/L TBT, and negative effects on ecologically relevant end points (e.g., decreased lifespan and fecundity) were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 66 publications
0
9
0
Order By: Relevance
“…Our results demonstrated that the interaction of TBT with RXR is conserved among Metazoa, with the exception of Placozoa (T. adhaerens) ( Figure 6). Moreover, we found that the condition described in rotifers [40] is not unique, since the cnidarian A. aurita RXR lacks the key cysteine and was nonetheless activated by TBT. The bryozoan B. neritina RXRs, on the other hand, yielded puzzling results, as similar responses were found independently of the conservation status of the cysteine residue.…”
Section: Discussionmentioning
confidence: 84%
See 3 more Smart Citations
“…Our results demonstrated that the interaction of TBT with RXR is conserved among Metazoa, with the exception of Placozoa (T. adhaerens) ( Figure 6). Moreover, we found that the condition described in rotifers [40] is not unique, since the cnidarian A. aurita RXR lacks the key cysteine and was nonetheless activated by TBT. The bryozoan B. neritina RXRs, on the other hand, yielded puzzling results, as similar responses were found independently of the conservation status of the cysteine residue.…”
Section: Discussionmentioning
confidence: 84%
“…Furthermore, the evolutionary conservation of RXR-dependent modulation by organotins was suggested among lophotrochozoans, vertebrates, and crustaceans [27,33,65]. Recently, an RXR-dependent signaling pathway was suggested to promote the changes in the fatty acid profiles of the rotifer B. koreanus exposed to TBT [40]. The Organisation for Economic Co-operation and Development (OECD) suggests in vitro assays as a level 2 approach to test and assess endocrine disruption by environmental contaminants and denotes NRs as key players in this framework [17].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This assumption is corroborated by the fact that concomitant significant increase the relative mRNA levels of RXR and RAR, known to act as heterodimers (Germain et al 2003), have been observed after 24 h of exposure to flutamide or cyproterone acetate. Moreover, Bettin et al (1996) shown in gastropods that cyproterone acetate was able to inhibit imposex induction by TBT, known to act through RXR pathways (Abidli et al 2013;Lee et al 2019;Nishikawa et al 2004;Lima et al 2011;Stange et al 2012). Similar profiles of expression after 24 h of exposure could result from a change in the metabolism of the 9-cis-retinoid acid which can bind to both RAR and RXR.…”
Section: Discussionmentioning
confidence: 97%